Hubungan Penyakit Infeksi Cacing Terhadap Status Gizi Pada Anak Panti Asuhan Di Kecamatan Medan Sunggal - Cut Maqfirah; Yeni Halim; Irza Haicha Pratama (Lembaga Pengembangan Kinerja Dosen, 2024)
Worm infections are the entry of worm eggs into the human body and multiply, causing disease. A worm infection is declared positive if worm eggs are found in at least one type of worm in the specimen examined. Worm infections can cause malnutrition because all the nutrients will be absorbed by the worms which will ultimately cause the child's mental and physical development to be disrupted, children become sick easily due to a decrease in the immune system, stunting or short stature and being smaller than their peers, and reduced intelligence and Some cases can cause death in children. The aim of this research is to determine the relationship between worm infections and nutritional status in children in orphanages. This research is an analytical observational study using a cross sectional method. The population in this study was all 33 children from the Al-Marhamah orphanage and all 42 children from the Cinta Kasih orphanage. In taking samples using a simple random sampling technique so that the sample in this study consisted of 63 samples consisting of 28 people at the Al-Marhamah orphanage and 35 people at the Cinta Kasih orphanage. Data analysis in this study used univariate and bivariate analysis. The results showed that 53 children were negative for worm infections with a percentage of 84.1%, 1 child was infected with Ascaris worms with a percentage of 1.6% and 9 children were infected with Trishiuris worms with a percentage of 14. 3%. In this study, the type of worm that was often found in children from orphanages in Medan Sunggal District was the Trishiuris worm type. The description of the nutritional status of children who have worm infections is 10 children with poor nutrition, 16 with moderate nutrition, 17 with moderate nutrition, 18 with good nutrition and 2 with over nutrition. The conclusion of this study is that there is no significant relationship between worm infections and the nutritional status of children in the Cinta Kasih and AL – Marhamah orphanages (p>0.05).